PENGEMBANGAN REALQU UNTUK MEMAKSIMALKAN KEMAMPUAN PEMBUKTIAN MATEMATIS BERDASARKAN ADVERSITY QUOTIENT - Era Dewi Kartika; Dyah Ayu Sulistyaning Cipta; Laila Nur Rohmah (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The Covid-19 pandemic, which has an impact on the application of online learning, requires teachers to find the right learning methods and strategies. In this study, researchers used RealQu, an application created using Figma and Android Studio. By using RealQu, the Real Analysis learning that is carried out is expected to be able to maximize students' mathematical proof abilities based on the adversity quotient. The research method used is development research which produces a product called RealQu which can be installed on Android-based phones. From the trial results, it was concluded that RealQu could then be used in Real Analysis lectures that still used the system in the network. There is an increase in students' abilities in the quitter, camper, and climber categories.